Graduate Education in Sub-Saharan Africa - Hayward, Fred (International Higher Education, 2012)
An examination of some of the challenges facing graduate education in Sub-Saharan Africa which traces the decline in higher education in much of Africa, describes problems hindering quality graduate education, the need to recreate the culture of research that existed earlier, and makes some suggestions about ways to promote and expand high quality graduate education on a regional basis.